ROTI DALAM TEOLOGI: Simbol Makanan sebagai Teologi Tubuh dan Keberlangsungan Hidup - Sri Sela; Greinviola; Jesliani; Devi Taura Maharani; Elma Manda' Sendana (CV. ADIBA AISHA AMIRA, 2025)
This paper explores the symbol of bread in Christian theology as an entry point to reflect on the relationship between the body, faith, and the sustainability of life. Bread is not merely food but also a sign of divine provision, the fellowship of believers, and the presence of Christ in the world. This research employs a literature review method by examining biblical sources, classical theological reflections such as the thoughts of John Calvin, and contemporary developments in food justice discourse. The symbolism of bread is analyzed across various dimensions: as a basic human need, a theological act in the Eucharist, a symbol of the unity of Christ’s body, and its meaning within socio-ecological contexts. Amid global food crises and unequal distribution, theological reflection on bread challenges the church and believers to embody a grounded faith, compassion, and active participation in defending shared human dignity. This paper offers the perspective that eating is not merely a physical act, but a theological one that unites the body, love, and justice.